ANÁLISE DA EXPRESSÃO GÊNICA DA CARTILAGEM DE FRANGOS DE CORTE NORMAIS E AFETADOS COM NECROSE DA CABEÇA DO FÊMUR AOS 21 DIAS DE IDADE - SANTOS, CARLOS EDUARDO DOS (2021)
Brazil is the largest poultry exporter worldwide, with third largest breeding stock among all poultry producing countries. Locomotor problems can directly affect animal welfare by decreasing production and the comfort of animals. The main locomotor problems that affect broilers are Femoral Head Necrosis (FHN) also known as, Bacterial Chondronecrosis with Osteomyelitis (BCO). Although the etiology of this disorder is still unclear, some candidate genes associated with this problem have been described. In order to investigate the genes related to cartilage involved with FHS, the aim of this study was to identify differentially expressed genes in the articular cartilage of the normal and affected broilers at 21 days of age. 25 broilers with 21 days of age, 10 normal and 15 with visually locomotor problem. Out of those, the articular cartilage of 8 normal and 6 FHS-affected were collected for total RNA extraction. The quantitative PCR (qPCR) then used to analyze the expression of 15 candidate genes: ADA, ANGPTL5, AGNPTL7, ANK1, AVBD2, AVBD1, COL8A1, COL14A1, COL28A1, DPT, EPX, FBN2, IFI6, OPG and RHAG. The statistical analysis was performed using Mann Whitney test in the GraphPad program (Prism8). Five genes (ADA, AVBD2, RHAG, COL28A1 and ANGPTL7) were upregulated in FHS-affected compared to normal and group. At this earlier age, these results reinforce those genes as candidates to trigger FHN in chickens. Furthermore, the ADA and ANGPTL7 function in FHN should be further investigated in a larger population to verify their role in this condition. These results could also contribute to improve the knowledge on FHN etiology in other species, such as horse and pigs that are severely affect by bone disorders.